Tolerância do arroz irrigado ao herbicida clomazone pela ação de protetores de plântulas - Sanchotene, Danie Martini (2009)
Clomazone is a herbicide used for grass weed control in paddy rice. However, label rate may not provide efficient control for some weed species. For this reason many times it is necessity to increase the rate to improve weed control efficiency. Clomazone selectivity in rice is affected for soil type, the rate of the herbicide and the cultivar used, been necessary the use of safener to protect the plants when high rates are used. Though, it is necessary to adjust those factors for better use of this technology. For this reason, it were conducted two greenhouse experiments, the first with the objective of quantify the selectivity of clomazone in sand and clay soils, to quantify the protection of the dietholate on rice plants in these soil conditions. The second experiment had the objective of verify if phorate provides similar protective effect as dietholate provides for clomazone. The results allowed to conclude that the cultivars IRGA 409 and IRGA 417 are equally sensible to clomazone. In regards of soil type, clomazone cause higher injury to rice cultivated in sandy soil. The application of dietholate allows the increase of dose of clomazone. As much in the sandy soil as in the clay soil, dietholate as treatment of seeds allowed increase of the dose of clomazone in up to three times the dose in relation to the treatment without dietholate. Organophosphate phorate is capable to act as safener for rice when clomazone is applied, with similar safening ability as dietholate, conferring to the crop capability to support higher rates of clomazone.